Musyawarah Minim Negosiasi: Potret Deficient Village Governance pada Masa Pandemi COVID-19 - Sobari, Wawan (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
This study explored the practice of village governance (TKPD), particularly the practice of making village development policies during the COVID-19 pandemic (2020–2022) in Malang Regency, East Java. The policy-making was carried out in the village deliberation forum (musdes). This research specifically sought to discover the practice of musdes during the COVID-19 pandemic. It applied a qualitative methodology and an observational analysis method, with the interview as the main data-gathering technique. This study reveals changes in the practice and meaning of musdes in setting village development policies. The pandemic situation has forced the government to drive village development policy options that are not fully in accordance with the needs and demands of villagers. Musdes has changed its meaning. It is no longer a space for consultation and negotiation. Musdes become a non-deliberative forum that functions for clarification and approval of village development policies that have been directed by government and regency regulations.  This finding reinforces previous studies that the village law and implementing regulations experience critical differences from musdes as a deliberation space because it reduces representation of the community and actors who can be involved in decision-making. The exploration of the practice and meaning of musdes during the COVID-19 pandemic adds to the village governance literature, which was different from the situation prior to the pandemic. At that time, the village government still had enough space to accommodate the villagers' demands. This study echoes the state-centered approach to explaining village governance by discovering the government as an obstacle to village governance. This study also contributes to extending village governance literature by proposing the worth of considering an antecedent factor that encourages the government and regency to issue regulations that do not support village governance. The context of the pandemic can explain factors that occurred prior to the issuance of government regulation, which then hindered village governance.